Late Pliocene Marine pCO2 Reconstructions From the Subarctic Pacific Ocean. Issue 5 (16th May 2018) - Swann, George E. A.; Kendrick, Christopher P.; Dickson, Alexander J.; Worne, Savannah
Abstract: The development of large ice sheets across the Northern Hemisphere during the late Pliocene and the emergence of the glacial‐interglacial cycles that punctuate the Quaternary mark a significant threshold in Earth's climate history. Although a number of different mechanisms have been proposed to initiate this cooling and the onset of major Northern Hemisphere glaciation, reductions in atmospheric concentrations of CO2 likely played a key role. The emergence of a stratified (halocline) water column in the subarctic northwest Pacific Ocean at 2.73 Ma has often been interpreted as an event which would have limited oceanic ventilation of CO2 to the atmosphere, thereby helping to cool the global climate system. Here diatom carbon isotopes (δ 13 Cdiatom ) are used to reconstruct changes in regional carbon dynamics through this interval. Results show that the development of a salinity stratification did not fundamentally alter the net oceanic/atmospheric flux of CO2 in the subarctic northwest Pacific Ocean through the late Pliocene/early Quaternary. These results provide further insights into the long‐term controls on global carbon cycling and the role of the subarctic Pacific Ocean in instigating global climatic changes. Key Points: Subarctic Pacific Ocean carbon dynamics is reconstructed using diatom carbon isotopes Net ocean‐atmosphere CO2 flux does not alter over the onset of major Northern Hemisphere Glaciation (circa 2.75–2.73 Ma)